Luminescence studies on BaSi6N8O: Eu3+ phosphors. Issue 4 (15th June 2016) - Fartode, S. A.; Reddy, B. Sudhakar; Nayar, V.; Dhoble, S.J.
ABSTRACT: This paper reports on the BaSi6 N8 O:Eu 3+ phosphor were prepared via modified two steps solid state diffusion technique in open air atmosphere and material was quenched at 1200 ° C for four hours. Eu 3+ activated BaSi6 N8 O phosphor was characterized by XRD, which confirms the formation of the sample. From the Scanning electron microscope (SEM) images, the surface morphology of the sample has been studied. The photoluminescence (PL) spectra of BaSi6 N8 O:Eu 3+ phosphor exhibits two emission bands at 614 nm ( 5 D0 → 7 F2 ) and at 587 nm ( 5 D0 → 7 F1 ) with an excitation wavelength of 396 nm. From the FTIR spectrum, bonding of atoms to each other and vibrational motions of molecules has been studied. ML was studied by dropping a piston on irradiated sample. From the ML glow curves single peak has been observed. ML intensity increases with activator concentration. Optimum ML has been observed for the sample having 1mole % of Eu ions.